2017
DOI: 10.1103/physreve.95.042135
|View full text |Cite
|
Sign up to set email alerts
|

Temperature of a single chaotic eigenstate

Abstract: The onset of thermalization in a closed system of randomly interacting bosons at the level of a single eigenstate is discussed. We focus on the emergence of Bose-Einstein distribution of single-particle occupation numbers, and we give a local criterion for thermalization dependent on the eigenstate energy. We show how to define the temperature of an eigenstate, provided that it has a chaotic structure in the basis defined by the single-particle states. The analytical expression for the eigenstate temperature a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…This energy is higher by some amount ∆ α than the eigenvalue E α , in the region where the density of states increases, see Ref. [18]. Correspondingly, the effective temperature T dres is higher than that obtained with E α .…”
Section: Single-particle Occupation Numbersmentioning
confidence: 86%
“…This energy is higher by some amount ∆ α than the eigenvalue E α , in the region where the density of states increases, see Ref. [18]. Correspondingly, the effective temperature T dres is higher than that obtained with E α .…”
Section: Single-particle Occupation Numbersmentioning
confidence: 86%
“…To date it is understood that the validity of statistical mechanics can be justified not only by averaging over a number of eigenstates with close energies, but also with the use of a single eigenstate if the latter consists of many uncorrelated components in the physically chosen basis. Specifically, it was shown that BE and FD distributions emerge also on the level of individual eigenstates if they are strongly chaotic [8,10,11]. The most intriguing point here is that both distributions appear even if the number of particles is small; this happens due to the fast growth of the number of components in many-body eigenstates in dependence on the number of particles.…”
mentioning
confidence: 80%
“…One of the basic statistical properties of many-body systems is either the Bose-Einstein (BE) or Fermi-Dirac (FD) distribution that emerge in the thermodynamic limit due to the combinatorics and without inter-particle interaction. As for finite isolated systems, the mechanism for the onset of BE and FD distributions is the chaotic structure of many-body eigenstates [3,5,[7][8][9][10]. In this case, the interaction between particles plays a crucial role: the fewer the particles the stronger the inter-particle interaction has to be for the emergence of the statistical properties.…”
mentioning
confidence: 99%
“…Notwithstanding this, the ingredients indispensable for this emergence remain an open problem. It has been shown that the direct interaction between particles, via driving many-body quantum chaos, gives rise to complex structures of eigenstates, from which the Fermi-Dirac (FD) and Bose-Einstein (BE) distributions arise [3,10,13,14]. The need of this interaction conforms to standard statistical mechanics [15].…”
mentioning
confidence: 94%